(untitled) (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2023)
The aims of this study are to determine whether the use of the Rotating Trio Exchange (RTE) cooperative learning model has an effect on the learning outcomes of eighth grade students of MTs Negeri 2 Kotabaru. To determine whether the use of the Rotating Trio Exchange (RTE) cooperative learning model affect the social attitudes of class VIII students at MTs Negeri 2 Kotabaru. The method used in this research is an experimental quantitative research method. The research design used is the Pre-Experimental Design One-Group Pretest-Posttest Design. The sample amounted to 32 people from 123 people total population. Data were collected using research instruments in the form of learning outcomes tests and questionnaires.The results of this study are (1) the use of the Rotating Trio Exchange (RTE) Cooperative Learning Model has an effect on the learning outcomes of students in Class VIII B of MTsN 2 Kotabaru by 1.8%. (2) The use of the Rotating Trio Exchange (RTE) Cooperative Learning Model has an effect on the social attitudes of students in Class VIII B of MTsN 2 Kotabaru by 9.3%.Keywords: Effect, RTE Cooperative Type, Learning Outcomes, Social Attitude